Pengaruh Latihan 3 Cone Wall Passing dan “V” Roll To Gated Pass Terhadap Akurasi Passing Bawah - Noor Akhmad; Adi Suriatno (Universitas Pendidikan Mandalika, 2021)
Football is also one of the sports in West Nusa Tenggara Province which is very popular among the people. The highest achievement ever inscribed by the West Nusa Tenggara Football sport was participating in the Riau National Sports Week (PON) in 2012. The purpose of the study was to determine the effect of 3 Cone Wall Passing and